Primary health care - Önal, Ayşe Emel (IntechOpen, 2022)
This book presents examples from various countries about the provision of health services at the primary care level. Chapters examine the role of professionals in primary healthcare services and how they can work to improve the health of individuals and communities. Written by authors from Africa, Asia, America, Europe, and Australia, this book provides up-to-date information on primary health care, including telehealth services in the era of COVID-19.
Keywords: Primary health care; Primary health care : Decision making